EVALUASI PENGEMBANGAN PRODUK MULTIMEDIAPEMBELAJARAN - Miyarso, Estu (MAJALAH ILMIAH PEMBELAJARAN, 2018)
Evaluation of multimedia product development function to determine the extent towhich learning objectives have been achieved effectively and efficiently. Evaluationof multimedia product development includes the evaluation of the documents(production process), formative evaluation (airworthiness of products, summativeevaluation (effectiveness of the product), and evaluation of the impact on the user.Components of multimedia products which evaluated the learning componentconsists of aspects of the content and curriculum, while the components ofmultimedia products consists of the display and programming aspects.